New Classes of Generalized Seminormed Difference Sequence Spaces. (1st June 2014) - Mursaleen, M.; Alotaibi, A.; Sharma, Sunil K.
Abstract : The purpose of this paper is to introduce new classes of generalized seminormed difference sequence spaces defined by a Musielak-Orlicz function. We also study some topological properties and prove some inclusion relations between resulting sequence spaces.